The Sentinel Wires Technique for Safe Open Wedge High Tibial Osteotomy - Hesham Mohamed Gawish, M.D.; Mohamed Abdelmonsef Ibrahim Elghaish, M.Ch.(ortho); Waleed Hamed Hamed Ebrahim Aziz, M.Ch.(ortho); Mohamed Elfekky, M.Ch.(ortho); Ahmed Hassan Saad Abou Helwo, M.Ch.(ortho); Ahmed Hassan Taha Waly, M.D. (Arthroscopy Techniques)
Open wedge high tibial osteotomy is an effective surgical procedure for the treatment of medial compartment arthritis. Takeuchi described 3 types of lateral hinge fractures that may jeopardize the stability of the osteotomy with undesirable outcomes. In this Technical Note, 3 protective K-wires were implemented to improve lateral hinge resistance to failure.